2003
DOI: 10.1097/01.asn.0000050760.87113.25
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer-Induced Local Heme Oxygenase-1 Overexpression Protects Rat Kidney Transplants From Ischemia/Reperfusion Injury

Abstract: Abstract. Heme oxygenase-1 (HO-1) overexpression using gene transfer protects rat livers against ischemia/reperfusion (I/R) injury. This study evaluates the effects of Ad-HO-1 gene transfer in a rat renal isograft model. Donor LEW kidneys were perfused with Ad-HO-1, Ad-␤-gal, or PBS, stored at 4°C for 24 h, and transplanted orthotopically into LEW recipients, followed by contralateral native nephrectomy. Serum creatinine, urine protein/creatinine ratios, severity of histologic changes, HO-1 mRNA/protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 45 publications
7
75
0
1
Order By: Relevance
“…This suggests that HO-1 induction is not only T cell-dependent, but operational HO-1 cytoprotection does require the blockade of Stat4 signaling. We have shown that pharmacologic or gene therapyinduced HO-1 overexpression prevents hepatic 10,33 cardiac 34 and renal 35 I/R injury. Because HO-1 has been identified as a downstream effector of IL-10, 36 we then asked whether or not HO-1 may have been involved in Stat4 disruption-mediated effects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that HO-1 induction is not only T cell-dependent, but operational HO-1 cytoprotection does require the blockade of Stat4 signaling. We have shown that pharmacologic or gene therapyinduced HO-1 overexpression prevents hepatic 10,33 cardiac 34 and renal 35 I/R injury. Because HO-1 has been identified as a downstream effector of IL-10, 36 we then asked whether or not HO-1 may have been involved in Stat4 disruption-mediated effects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies examined the role of HO-1 and CO in kidney injury, and the functional role of CO in the context of renal fibrosis has not been previously examined. HO-1 overexpression or CO administration has been shown to protect experimental kidney transplants from ischemia-reperfusion injury (4,30). Moreover, the administration of CO donor compounds, namely carbon monoxide-releasing molecules (CORM-3), protected against cisplatin nephrotoxicity and ischemia-reperfusion-induced renal injury (44,47).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][28][29][30] In most of these studies, the introduction of HO-1 in grafts is achieved by metalloporphyrin (mainly cobalt protoporphyrin), gene transfer or transgenic engineering. These methods need to treat grafts in advance or are limited on transgenic animal models.…”
Section: Discussionmentioning
confidence: 99%